2010
DOI: 10.1007/s11033-010-0312-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the QM gene from Penaeus monodon and its expression on the different ovarian stages of development

Abstract: In present study, a QM gene was obtained from the ovary and neurosecretory organ in eyestalk cDNA library of black tiger prawn (Penaeus monodon). The full-length black tiger prawn QM (PmQM) cDNA contained a 5'-UTR of 41 bp, an ORF of 663 bp encoding a polypeptide of 220 amino acids with molecular weight 25.5 kDa, and a 3'-UTR of 54 bp. Homology analysis of the deduced amino acid sequence of the PmQM with other known QM sequences by MatGAT software revealed that the PmQM was high homology with other invertebrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Studies of the QM-like gene in aquatic organisms have focused on shellfishes (Oh et al, 2010), crustaceans (Xu et al, 2008;Zhou et al, 2011), and freshwater fishes (Wen et al, 2005). Increasing evidence has shown that the QM-like gene has important immune functions in organisms (Wen et al, 2005;Rocha et al, 2008;Oh et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the QM-like gene in aquatic organisms have focused on shellfishes (Oh et al, 2010), crustaceans (Xu et al, 2008;Zhou et al, 2011), and freshwater fishes (Wen et al, 2005). Increasing evidence has shown that the QM-like gene has important immune functions in organisms (Wen et al, 2005;Rocha et al, 2008;Oh et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In the Pacific blue shrimp Penaeus stylirostris , elongation factor 1 alpha ( EF-1α ) and glyceraldehydes-3 phosphate dehygrogenase ( GAPDH ) have been validated as reference genes for expression analysis of immune genes [13]. In the black tiger shrimp ( P. monodon), several housekeeping genes, such as β-actin [14], [15], [16], EF-1α [ 17 ], [18], [19], [ 20 ], GAPDH [19], 40S rRNA [21], 18S rRNA [16], [22], and elongation factor 2 [23] have been used as an internal control for qPCR. However, to date, no study has validated their suitability as an internal control for gene expression analysis using qPCR in P. monodon .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, research on the exact role of QM in marine invertebrate is also in its infancy. To date, a few QM genes have been reported in marine invertebrates, including L. vannamei [24], M. japonicus [15], P. monodon [31], and H. discus discus [23]. The present study is the first to report on the QM gene from scallop.…”
Section: Discussionmentioning
confidence: 65%
“…Different letters indicate significant differences (P < 0.05) determined by one-way ANOVA and Duncan's multiple comparisons. protein is involved in the innate immunity response mechanism of invertebrates, such as the activation of the proPO system as a critical enzyme [24,31]. In L. vannamei, the QM gene is upregulated in various tissues, such as hemolymph, hepatopancreas, gill, heart, intestine, and muscle, after infection with WSSV and V. anguillarum [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation